Label-Free Ratiometric Homogeneous Electrochemical Strategy Based on Exonuclease III-Aided Signal Amplification for Facile and Rapid Detection of miR-378 - Bingyuan Fan; Qian Wang; Shan Wang; Yahui Gao; Yan Liang; Jinru Pan; Xinrui Fu; Li Li; Wei Meng (International Journal of Analytical Chemistry)
MiR-378 is abnormally expressed in various cancers, such as hepatocellular carcinoma, renal cell carcinoma, and nonsmall cell lung cancer. Here, we developed a label- and immobilization-free ratiometric homogeneous electrochemical strategy based on exonuclease III (Exo III) for the facile and rapid determination of miR-378. Two 3′-protruding hairpin DNA probes (HPs) are designed in this strategy. Doxorubicin (DOX) and potassium ferrocyanide (Fe2+) were used as label-free probes to produce a response signal (IDOX) and a reference signal (IFe2+) in the solution phase. When no target was present in the solution, the HP was stable, most of the DOX was intercalated in the stem of the HP, and the diffusion rate of DOX was significantly reduced, resulting in reduced electrochemical signal response. When miR-378 was present, double-cycle signal amplification triggered by Exo III cleavage was initiated, ultimately disrupting the hairpin structures of HP1 and HP2 and releasing a large amount of DOX into the solution, yielding a stronger electrochemical signal, which was low to 50 pM. This detection possesses excellent selectivity, demonstrating high application potential in biological systems, and offers simple and low-cost electrochemical detection for miR-378.